Diagnostic Capabilities Of MRCP In Obstructive Jaundice - Nurmurzayev, Zafar (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Obstructive jaundice remains one of the most critical and challenging conditions in hepatobiliary surgery, often leading to progressive hepatic failure and severe metabolic disorders. Accurate and timely diagnosis of the site and cause of biliary obstruction determines the effectiveness of subsequent surgical or interventional treatment. The use of advanced radiological techniques — ultrasound (US), multislice computed tomography (MSCT), magnetic resonance cholangiopancreatography (MRCP), and endoscopic retrograde cholangiopancreatography (ERCP) — allows for detailed visualization of the biliary tract, identification of pathological changes, and assessment of hepatic function, thus playing a decisive role in clinical decision-making.